Warehouse Receipt System Policy for Aceh’s Gayo Coffee Farmers during COVID-19: An Overview of Maqāṣid Sharia - Andriani, Fitria; Maghfirah, Fitri (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2021)
This study aims to describe three discussion topics about the importance of the coffee commodity for the Gayo community, the impact of COVID-19 on Gayo coffee farmers, and to analyse the policies implemented by the government in minimizing the losses of farmers affected by COVID-19 in the framework of maqāṣid sharia. This type of research is qualitative, with data methods through in-depth literature reviews of primary and secondary sources of previous scientific research, government agency reports and online media. The results showed that Gayo coffee has made a major contribution to food security, but since Covid-19 it has implications for coffee price fluctuations which have an impact on decreasing people’s income. Therefore, the government issued a Warehouse Receipt System policy, with the aim that Gayo coffee farmers could use warehouse receipts to obtain financing facilities from banks in financing food security and coffee production needs. The policy taken by the government in minimizing the risk of loss for Gayo coffee farmers is a manifestation of the value of the maqāṣid sharia values in maintaining self-preservation (ḥifẓ nafs) and preserving property (ḥifẓ Mal) so that they can continue to survive in order to maintain welfare even during the pandemic. This effort can also be used to strengthen the Gayo coffee production chain because in addition to obtaining financing to meet production needs, it can also be used to meet food during a crisis.